65 years of the double helix : the advancements of gene editing and potential application to hereditary cancer - Tan, Zi Ying (2020)
Hereditary cancer predisposition syndromes are associated with germline mutations that lead to increased vulnerability for an individual to develop cancers. Such germline mutations in tumour suppressor genes, oncogenes and genes encoding for proteins essential in DNA repair pathways and cell cycle control can cause overall chromosomal instability in the genome and increase risk in developing cancers. Gene correction of these germline mutations to restore normal protein functions is anticipated as a new therapeutic option. This can be achieved through disruption of gain-of-function pathogenic mutation, restoration of loss-of-function mutation, addition of a transgene essential for cell function and single nucleotide changes. Genome editing tools are applicable to precise gene correction. Development of genome editing tools comes in two waves. The first wave focuses on improving targeting specificity and editing efficiency of nucleases, and the second wave of gene editing draws on innovative engineering of fusion proteins combining deactivated nucleases and other enzymes that are able to create limitless functional molecular tools. This gene editing advancement is going to impact medicine, particularly in hereditary cancers. In this review, we discuss the application of gene editing as an early intervention and possible treatment for hereditary cancers, by highlighting a selection of highly penetrant cancer syndromes as examples of how this may be achieved in clinical practice.